1997
DOI: 10.1038/bjc.1997.173
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic studies of human primitive neuroectodermal tumour cells by proton nuclear magnetic resonance spectroscopy

Abstract: Summary Well-characterized cell lines established from primitive neuroectodermal tumours (PNETs) were examined by proton nuclear magnetic resonance ('H-NMR) spectroscopy and chromatographic analysis of perchloric acid extracts, following amplification in cell culture. A characteristic 'H-NMR spectroscopic metabolite pattern was found for medulloblastoma cell lines, which clearly discriminates these cells from PNETs of other locations in the central nervous system (CNS), on the basis of their N-acetyl aspartate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…This finding is consistent with a predominant contribution from PCh in the medulloblastomas and a more even distribution of choline-containing compounds in the astrocytomas and ependymomas. High [PCh] in medulloblastomas is supported by the HR-MAS findings, a previous study using 31 P MRS in vivo (34) and is consistent with studies of medulloblastoma cell cultures (35).…”
Section: Tumour Characterisationsupporting
confidence: 89%
“…This finding is consistent with a predominant contribution from PCh in the medulloblastomas and a more even distribution of choline-containing compounds in the astrocytomas and ependymomas. High [PCh] in medulloblastomas is supported by the HR-MAS findings, a previous study using 31 P MRS in vivo (34) and is consistent with studies of medulloblastoma cell cultures (35).…”
Section: Tumour Characterisationsupporting
confidence: 89%
“…Multivariate analysis was performed using SIMCA-P version 12.0 (Umetrics). Metabolite chemical shifts were assigned using Chenomx NMR suite version 6.1 (Chenomx Inc.) and literature 51 52 53 , and their identities were confirmed based on total correlation spectroscopy (2D 1 H– 1 H TOCSY) and spiking experiments. Quantification was achieved using the 600 MHz library from Chenomx NMR Suite version 6.1 which uses the concentration of a known reference signal (TSP-d 4 ) to determine the concentration of individual compounds.…”
Section: Methodsmentioning
confidence: 99%
“…1 H NMR studies of extracts of (non-infected) erythrocytes from a range of species have revealed the presence of over 50 metabolites (11). A similar number were identified in 1 H NMR studies of lymphocyte extracts (12) and plant cell cultures (13), and somewhat fewer in 1 macrophages (14), cancer cells (15)(16)(17)(18), and plant tissue [reviewed in Ref. (19)].…”
Section: Introductionmentioning
confidence: 96%